IMPLEMENTASI NILAI KEAGAMAAN DALAM SISTEM FULL DAY SCHOOL DAN BOARDING SCHOOL DI SMP IT SUMATERA SELATAN - Mansur, Abu; Nurani, Qoim (Tadrib: Jurnal Pendidikan Agama Islam, 2022)
This study aims to describe, analyze and interpret the religious values ​​implemented in SMP IT South Sumatra. This research is a comparative descriptive study. The sample in this study was determined by purposive sampling, namely SMP IT Izzuddin Palembang, SMP IT Raudlatul Ulum Ogan Ilir and SMP IT An-Nida Lubuk Linggau. Data collection using observation, interview and documentation techniques. The data analysis technique was carried out by combining the Creswell and Mathew and Huberman models by carrying out three stages, namely data reduction, data display and interpretation. To check the validity of the data, triangulation was carried out. The results showed that: First, the implementation of religious values ​​through three values, namely the value of faith, the value of worship and the value of morals. These three values ​​are all applied in SMP IT either on the basis of Full Day School or Boarding School. The implementation is through cognitive aspects in the form of an understanding of faith, worship and morals through the subjects taught, namely Akidah Akhlak and Fiqih; through affective aspects, namely through role models so that students feel that the good things that are seen must be followed; as well as the psychomotor aspect with habituation of activities that contain the values ​​of faith, worship and morals, namely habituation of midnight prayers, congregational prayers and tadarus al-Qur'an. Second, SMP IT in South Sumatra, both Boarding School and Full Day, has similarities in the implementation of religious values ​​from the same source, namely the JSIT curriculum which is implemented in the vision, mission and objectives of SMP IT. Meanwhile, the difference between Boarding and Full Day is when the implementation is more intense which can be done by Boarding-based SMPIT managers. The findings in this study are that the value of habituation and modeling are the main bases in the implementation of religious values ​​in schools.